SELF-MANAGEMENT: PERSPEKTIF PRESTASI AKADEMIK DAN GENDER MAHASISWA - Ririen, Deci (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Students must have good self-management and have a strong will to be able to solve problems faced during college in an effort to achieve study success. The purpose of this study was to analyze the level of student self-management reviewed from the perspective of academic ability and gender. This study is a quantitative descriptive study. The respondents in this study were students of the Indragiri Rengat Institute of Technology and Business aged 18–24 years totaling 212 people. The findings of this study include: students' self-management ability for the self-motivation component in the good category. Students' self-management ability for the self-control component in the sufficient category. Students who have higher academic achievement have better self-management than students with low academic achievement. There are differences based on gender in aspects of self-management, especially in self-motivation and self-control. Men have higher scores than women in both aspects